Modeling of gyroidal mesoporous CMK-8 and CMK-9 carbon nanostructures and their X-Ray diffraction patterns - Schwind, Bertram; Smått, Jan-Henrik; Tiemann, Michael; Weinberger, Christian (Microporous and Mesoporous Materials)
Powder X-ray diffraction (XRD) patterns of ordered mesoporous CMK-8 and CMK-9 carbon materials are simulated by geometric modeling. The materials are amorphous at the atomic length scale but exhibit highly symmetric gyroidal structures at the nanometer scale, corresponding to regular, continuous nanopore systems with cubic symmetry. Their structures lead to characteristic low-angle XRD signatures. We introduce a model based on geometrical considerations to simulate CMK-8 and CMK-9 structures with variable volume fraction of carbon (vs. pore volume, i.e., variable 'pore wall thickness'). In addition, we also simulate carbon materials with variable amounts of guest species (e.g., sulfur) residing in their pores. The corresponding XRD patterns are calculated. The carbon volume fraction turns out to have a significant impact on the relative diffraction peak intensities, especially in case of CMK-9 carbon that features a bimodal porosity. Likewise, the presence of guest species in the pores may also strongly affect the relative peak intensities. Our study suggests that careful evaluation of experimental low-angle XRD patterns of (real) CMK-8 or CMK-9 materials offers an opportunity to obtain detailed information about the nanostructural properties in addition to the mere identification of the pore systems geometry.

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos, Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)
A comparison of infrared spectroscopic analytical approaches was made in order to assess their applicability for internal structure characterization of SiO2 thin films. Markers for porosity and/or disorder based on the analysis of the asymmetric stretching absorption band of SiO2 between 900−1350 cm−1 were discussed. The shape of this band, which shows a well-defined LO–TO splitting, depends not only on the inherent characteristics of the film under analysis but also on the particular geometry of the IR experiment and the specific surface selection rules of the substrate. Three types of SiO2 thin films with clearly defined porosity ranging from dense films to mesoporous films were investigated by transmission (at different incidence angles), direct specular reflection (at different angles), and diffuse reflection. Two different types of substrate, metallic and semiconducting, were used. The combined effect of substrate and specific technique in the final shape of the band, was discussed, and the efficacy for their applicability to the determination of porosity in thin SiO2 films was critically evaluated.

Selective Modification of Hierarchical Pores and Surfaces in Nanoporous Materials - Tiemann, Michael; Weinberger, Christian (Advanced Materials Interfaces)
Tailor-made ordered mesoporous materials bear great potential in numerous fields of application where large interfaces are required. However, the inherent surfacechemical properties of conventional materials, such as silica, carbon or organosilica, poses some limitations with respect to their application. Surface manipulation by functionalization with chemically more reactive groups is one way to improve materials for their desired purpose. Another approach is the design of high surface-area composite materials. The surface manipulation, either by functionalization or by introducing guest species, can be performed selectively. This means that when several distinct, i.e. , hierarchical, types of surfaces or pore systems exist in a material, each of them may be chosen for manipulation. Several strategies can be identified to achieve this goal. Molecules or molecule assemblies can be utilized to temporarily protect pores or surfaces (soft protection), while manipulation occurs at the accessible sites. This approach is a recurring motive in this review and can also be applied to rigid template matrices (hard protection). Furthermore, the size of functionalization agents (size protection) and their reactivity/diffusion (kinetic protection) into the pores can also be utilized to achieve selectivity. In addition, challenges in the synthesis and characterization of selectively manipulated ordered mesoporous materials are discussed.

Examination of the evolution of iron oxide nanoparticles in flame spray pyrolysis by tailored in situ particle sampling techniques - Tischendorf, R.; Simmler, M.; Weinberger, Christian; Bieber, M.; Reddemann, M.; Fröde, F.; Lindner, J.; Pitsch, H.; Kneer, R.; Tiemann, Michael; Nirschl, H.; Schmid, H.-J. (Journal of Aerosol Science)
In this report, a flame spray pyrolysis setup has been examined with various in situ extraction methods of particle samples along the flame axis. First, two precursor formulations leading to the formation of iron oxide nanoparticles were used in a standardized SpraySyn burner system, and the final particle outcome was characterized by a broad range of established powder characterization techniques (TEM/HRTEM, SAXS, XRD, BET). The characterization of the powder products evidenced that mostly homogeneous gas-to-particle conversion takes place when applying an acidic precursor solution, whereas the absence of the acid leads to a dominant droplet-to-particle pathway. Our study indicates that a droplet-to-particle-pathway could be present even when processing the acidic formulation. However, even if a secondary pathway might take place in this case as well, it is not dominant and nearly negligible. Subsequently, the in situ particle structure evolution was investigated for the dominant gas-to-particle pathway, and particles were extracted along the flame axis for online SMPS and offline TEM/HRTEM analysis. Due to the highly reactive conditions within the flame (high temperatures, turbulent flow field, high particle number concentrations), the extraction of representative samples from spray flames is challenging. In order to handle the reactive conditions, two extraction techniques were tailored in this report. To extract an aerosol sample within the flame for SMPS measurement, a Hole in a Tube probe was adjusted. Thus, the mobility particle diameter as well as the corresponding distribution widths were obtained at different heights above the burner along the flame axis. For TEM/HRTEM image analysis, particle samples were collected thermophoretically by means of a tailored shutter system. Since all sampling grids were protected until reaching the flame axis and due to the low sampling time, momentary captures of local particle structures could be extracted precisely. The particle morphologies have clearly shown an evolution from spherical and paired particles in the flame center to fractal and compact agglomerates at later synthesis stages.

TiO2 nanoparticle coatings on glass surfaces for the selective trapping of leukemia cells from peripheral blood - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Weinberger, Christian; Schwiderek, Sabrina; Knust, Steffen; Tiemann, Michael; Grundmeier, Guido; Keller, Adrian; Camargo Amado, Ruben Jesus (Journal of Biomedical Materials Research Part B: Applied Biomaterials)
Photodynamic therapy (PDT) using TiO2 nanoparticles has become an important alternative treatment for different types of cancer due to their high photocatalytic activity and high absorption of UV-A light. To potentiate this treatment, we have coated commercial glass plates with TiO2 nanoparticles prepared by the sol–gel method (TiO2-m), which exhibit a remarkable selectivity for the irreversible trapping of cancer cells. The physicochemical properties of the deposited TiO2-m nanoparticle coatings have been characterized by a number of complementary surface-analytical techniques and their interaction with leukemia and healthy blood cells were investigated. Scanning electron and atomic force microscopy verify the formation of a compact layer of TiO2-m nanoparticles. The particles are predominantly in the anatase phase and have hydroxyl-terminated surfaces as revealed by Raman, X-ray photoelectron, and infrared spectroscopy, as well as X-ray diffraction. We find that lymphoblastic leukemia cells adhere to the TiO2-m coating and undergo amoeboid-like migration, whereas lymphocytic cells show distinctly weaker interactions with the coating. This evidences the potential of this nanomaterial coating to selectively trap cancer cells and renders it a promising candidate for the development of future prototypes of PDT devices for the treatment of leukemia and other types of cancers with non-adherent cells.

New isoreticular phosphonate MOFs based on a tetratopic linker - Steinke, Felix; Javed, Ali; Wöhlbrandt, Stephan; Tiemann, Michael; Stock, Norbert (Dalton Transactions)
The tetratopic linker 1,1,2,2-tetrakis(4-phosphonophenyl)ethylene (H8TPPE) was used to synthesize the three new porous metal–organic frameworks of composition [M2(H2O)2(H2TPPE)]·xH2O (M = Al3+, Ga3+, Fe3+), denoted as M-CAU-53 under hydrothermal reaction conditions, using the corresponding metal nitrates as starting materials. The crystal structures of the compounds were determined ab initio from powder X-ray diffraction data, revealing small structural differences. Proton conductivity measurements were carried out, indicating different conductivity mechanisms. The differences in proton conductivity could be linked to the individual structures. In addition, a thorough characterization via thermogravimetry, elemental analysis, IR-spectroscopy as well as N2- and H2O-sorption is given.

Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii) complexes - Dierks, Philipp; Kruse, Ayla; Bokareva, Olga S.; Al-Marri, Mohammed J.; Kalmbach, Jens; Baltrun, Marc; Neuba, Adam; Schoch, Roland; Hohloch, Stephan; Heinze, Katja; Seitz, Michael; Kühn, Oliver; et al. (Chemical Communications)
Two closely related FeII complexes with 2,6-bis(1-ethyl-1H-1,2,3-triazol-4yl)pyridine and 2,6-bis(1,2,3-triazol-5-ylidene)pyridine ligands are presented to gain new insights into the photophysics of bis(tridentate) iron(II) complexes. The [Fe(N^N^N)2]2+ pseudoisomer sensitizes singlet oxygen through a MC state with nanosecond lifetime after MLCT excitation, while the bis(tridentate) [Fe(C^N^C)2]2+ pseudoisomer possesses a similar 3MLCT lifetime as the tris(bidentate) [Fe(C^C)2(N^N)]2+ complexes with four mesoionic carbenes.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composite; Metallkomplexe; Optical and Magnetic Materials; Catalysis

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michał; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
For entropic reasons, the synthesis of macrocycles via olefin ring-closing metathesis (RCM) is impeded by competing acyclic diene metathesis (ADMET) oligomerization. With cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) complexes confined in tailored ordered mesoporous silica, RCM can be run with macrocyclization selectivities up to 98% and high substrate concentrations up to 0.1 M. Molecular dynamics simulations show that the high conversions are a direct result of the proximity between the surface-bound catalyst, proven by extended X-ray absorption spectroscopy, and the surface-located substrates. Back-diffusion of the macrocycles decreases with decreasing pore diameter of the silica and is responsible for the high macrocyclization efficiency. Also, Z-selectivity increases with decreasing pore diameter and increasing Tolman electronic parameter of the NHC. Running reactions at different concentrations allows for identifying the optimum substrate concentration for each material and substrate combination.
Keywords: Catalysis; General Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michał; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Rh(I) NHC and Rh(III) Cp* NHC complexes (Cp*=pentamethylcyclopentadienyl, NHC=N-heterocyclic carbene=pyrid-2-ylimidazol-2-ylidene (Py−Im), thiophen-2-ylimidazol-2-ylidene) are presented. Selected catalysts were selectively immobilized inside the mesopores of SBA-15 with average pore diameters of 5.0 and 6.2 nm. Together with their homogenous progenitors, the immobilized catalysts were used in the hydrosilylation of terminal alkynes. For aromatic alkynes, both the neutral and cationic Rh(I) complexes showed excellent reactivity with exclusive formation of the β(E)-isomer. For aliphatic alkynes, however, selectivity of the Rh(I) complexes was low. By contrast, the neutral and cationic Rh(III) Cp* NHC complexes proved to be highly regio- and stereoselective catalysts, allowing for the formation of the thermodynamically less stable β-(Z)-vinylsilane isomers at room temperature. Notably, the SBA-15 immobilized Rh(I) catalysts, in which the pore walls provide an additional confinement, showed excellent β-(Z)-selectivity in the hydrosilylation of aliphatic alkynes, too. Also, in the case of 4-aminophenylacetylene, selective formation of the β(Z)-isomer was observed with a neutral SBA-15 supported Rh(III) Cp* NHC complex but not with its homogenous counterpart. These are the first examples of high β(Z)-selectivity in the hydrosilylation of alkynes by confinement generated upon immobilization inside mesoporous silica.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Immobilized Platinum Hydride Species as Catalysts for Olefin Isomerizations and Enyne Cycloisomerizations - Maier, Sarah; Cronin, Steve P.; Vu Dinh, Manh-Anh; Li, Zheng; Dyballa, Michael; Nowakowski, Michał; Bauer, Matthias; Estes, Deven P. (Organometallics)
Platinum hydride species catalyze a number of interesting organic reactions. However, their reactions typically involve the use of high loadings of noble metal and are difficult to recycle, making them somewhat unsustainable. We have synthesized surface-immobilized Pt–H species via oxidative addition of surface OH groups to Pt(PtBu3)2 (1), a rarely used immobilization technique in surface organometallic chemistry. The hydride species thus made were characterized by infrared, magic-angle spinning nuclear magnetic resonance, and X-ray absorption spectroscopies and catalyzed both olefin isomerization and cycloisomerization of a 1,6 enyne (5) with a high selectivity and low Pt loading.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry